2022
DOI: 10.1002/tpg2.20245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a genomic region containing genes involved in resistance to four pathotypes of Plasmodiophora brassicae in Brassica rapa turnip ECD02

Abstract: Clubroot, caused by Plasmodiophora brassicae, is an important disease of brassica crops worldwide. Vegetable turnip (Brassica rapa L.) have proven to be a source of clubroot resistance genes effective against many pathotypes of P. brassicae. The F 1 progeny from the cross B. rapa canola ACDC (susceptible, S) × B. rapa turnip ECD02 (resistant, R) were backcrossed with ACDC, then self-pollinated to produce BC 1 S 1 lines. All the F 1 plants were resistant to four pathotypes (3A, 3D, 3H, and 5X) of P. brassicae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
1
0
Order By: Relevance
“…'Mendel' was initially expected to possess three dominant CR genes inherited from its diploid parent ECD04 [58][59][60] . However, genetic mapping revealed that 'Mendel' had two dominant CR genes 61 , suggesting a potential loss of the other gene during the breeding process. Similar loss of CR genes has been reported in the breeding of a rutabaga line 62 .…”
Section: Kasp Resultsmentioning
confidence: 99%
“…'Mendel' was initially expected to possess three dominant CR genes inherited from its diploid parent ECD04 [58][59][60] . However, genetic mapping revealed that 'Mendel' had two dominant CR genes 61 , suggesting a potential loss of the other gene during the breeding process. Similar loss of CR genes has been reported in the breeding of a rutabaga line 62 .…”
Section: Kasp Resultsmentioning
confidence: 99%
“…Due to the rapid emergence of new pathotypes and the A-genome CR resistance breakdown in 1st generation CR cultivars, it becomes an urgency to utilize polygenic resistance of B. oleracea. Until now, most of the CR genes identified in Canada from A-genome of B. rapa (Yu et al 2017(Yu et al , 2016(Yu et al , 2021Chu et al 2014;Huang et al 2017;Gao et al 2014;Karim et al 2020;Rahaman et al 2022) andB. napus (Fredua-Agyeman et al 2016;Hasan et al 2016;Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…B. oleracea chromosomes C03 and C08 have higher synteny with B. rapa chromosomes A03 and A08, respectively (Perumal et al 2020). Many CR genes have been identified in chromosomes A03 and A08 (Yu et al 2021;Rahaman et al 2022). Two QTLs Rcr_C03-1 and Rcr_C08-1 with TNL or CNL genes identified in this study were compared with A03 and A08 of B. rapa using B. rapa reference genome sequence 'Chiifu' v3.0 (Zhang et al 2018).…”
Section: Identification Of Potential Candidates Genes For the Qtlsmentioning
confidence: 98%
“…rapa ) ( Yu et al , 2021 ; Yang et al , 2022 ). Most of the resistance loci have been mapped to chromosomes A01, A02, A03, A06, and A08 of the A genome, with only a few being mapped to the B or C genome ( Matsumoto et al , 1998 ; Suwabe et al , 2003 , 2006 ; Hirai et al , 2004 ; Piao et al , 2004 ; Sakamoto et al , 2008 ; Werner et al , 2008 ; Ueno et al , 2012 ; Chen et al , 2013 ; Hatakeyama et al , 2013 ; Chu et al , 2014 ; Li et al , 2016 ; Yu et al , 2016 , 2017 , 2021 ; Huang et al , 2017 , 2019 ; Hasan and Rahman, 2018 ; Hirani et al , 2018 ; Pang et al , 2018 ; Chang et al , 2019 ; Laila et al , 2019 ; Fredua-Agyeman et al , 2020 ; Karim et al , 2020 ; Dakouri et al , 2021 ; Rahaman et al , 2022 ). To date, only two clubroot-resistance genes, Crr1a and CRa , have been isolated, and they both encode toll-interleukin-1 receptor, nucleotide binding site, and leucine-rich repeat (TIR-NBS-LRR, TNL) proteins ( Ueno et al , 2012 ; Hatakeyama et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%